PENGARUH PENGALAMAN KERJA, INDEPENDENSI, DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI KOTA MEDAN - Hafsah Hafsah; Arfi Putri Prathita (CERED Indonesia Institute, 2026)
This study aims to test and analyze the influence of work experience, independence, and accountability on audit quality. In this study, the author uses an associative approach, with primary data as the data source. The data collection technique used was distributing questionnaires to 97 auditors working at Public Accounting Firms in Medan City. The sampling technique used was saturated sampling. The data analysis techniques used in this study were outer model analysis, inner model analysis, and hypothesis testing using Partial Least Square (PLS) software version 4.1.0.4. The results of this study indicate that: (1) Work experience has a significant effect on audit quality; (2) Independence does not have a significant effect on audit quality; (3) Accountability has a significant effect on audit quality.